ИМЕТО НА СКЕНДЕРБЕГ И НЕГОВОТО СЕМЕЈСТВО ВО ПРВИОТ ИСТОРИОГРАФСКИ ТРУД НА МАКЕДОНСКИ ЈАЗИК: (СПОРЕДБЕНА АНАЛИЗА СО ИЗВОРИТЕ) (Филолошке студије, 2019)
We are focused on Skenderbeg – a historical person from 15th century, Christian antiottoman ruler, who was successfully opposing the Ottoman Empire for a long time. In the tradition he was a hero, as a prime image in the Albanian, but also as a secondary image in the other Balkan traditions. We find data about him, his family and his rule in sources from different provenience, written with different alphabets and in various languages, and originating from Dubrovnik, Roma, Hilandar, Budim, Venetia, Milan etc. The Macedonian revival activist (revolutionary and cultural-national activist from 19th century) Georgia M. Pulevski was an author of the first history book in Macedonian language. He names Skenderbeg and his family sufficiently correct, taking into consideration the data from the sources, with Slavic names.